Depression as a cause and consequence of victimization - Spasić Danijela (Temida)
In this paper, I tried to show cause-and-consequence relationship between depression, as one of very frequent and specific mental disorders, and different forms of victimization. I wanted to make a modest contribution to the statement that depression, taken in a historic and temporal sequence despite our will and quite unexpectedly was transformed into some kind of "collective madness". At the beginning, it was a synonym for melancholy, a specific state into which those who were weaker were falling. But step by step and parallel with the global network of changes in all fields of human life, it got a character of world "infection" which spreading was being followed by the expansion of cardiovascular or malignant diseases, but without so obvious physical manifestations. Depression, as a long-term and "painful state of human soul" is often looking for shelter and rescue in abusing psychoactive substances, drugs and alcohols, and is often finding a way out in suicide behaviour, and therefore it becomes one of its dominant causes. Before that, it is, of course, usually manifested as a consequence of different forms of victimization; generally, it implies social conditions, either at macro or micro levels, and inadequate response of a person to them, but also criminal or any other negative acts, doings or omissions that could endanger or destruct any human good and put the man in a position of victim. In this way, depression "is closing its magic circle of causes and consequences", in which the man has three allies: himself community or other people, and time. Strength, quality and duration of allied assistance are reversely proportional to victimization dimension of depression.